Communication Regulatory Science: Mapping a New Field. Issue 3 (23rd February 2019) - Noar, Seth M.; Cappella, Joseph N.; Price, Simani
ABSTRACT: Communication regulatory science is an emerging field that uses validated techniques, tools, and models to inform regulatory actions that promote optimal communication outcomes and benefit the public. In the opening article to this special issue on communication and tobacco regulatory science, we 1) describe Food and Drug Administration (FDA) regulation of tobacco products in the US; 2) introduce communication regulatory science and provide examples in the tobacco regulatory science realm; and 3) describe the special issue process and final set of articles. Communication research on tobacco regulatory science is a burgeoning area of inquiry, and this work advances communication science, informs and potentially guides the FDA, and may help to withstand legal challenges brought by the tobacco industry. This research has the potential to have a major impact on the tobacco epidemic and population health by helping implement the most effective communications to prevent tobacco initiation and increase cessation. This special issue provides an example of 10 studies that exemplify tobacco regulatory science and demonstrate how the health communication field can affect regulation and benefit public health.